Money Politics from the Perspective of Ahmad Bahauddin Nursalim - Al Hashas, Mohammad Nasih (Nursyam Center, 2024)
This article aims to understand more about the phenomenon of money politics from the perspective of Ahmad Baharuddin Nursalim. He is one of the contemporary fiqh scholars. This type of research is qualitative-descriptive. In an effort to collect data, researcher used the literature study method on data related to the topics discussed in this article. The results of the research show that money politics is an activity that basically violates the rules of state law, violates religious propositions and is contrary to human nature. However, contemporary scholars such as Ahmad Bahauddin Nursalim consider that money politics is no longer categorised as “risywah” (something cursed by Allah and His messenger). The reason is that in this era there is a collective benefit that still needs to be fought using money politics, without money politics it is feared that this benefit will not be achieved and it is feared that it will cause a loss. For him, money politics is not only an activity that can be done by a good Muslim, but for the sake of the benefit of the people, money politics is an obligation for Muslims who are able to do it.